1999
DOI: 10.1046/j.1464-410x.1999.00088.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum insulin‐like growth factor‐1 is not a useful marker of prostate cancer

Abstract: Objective To determine whether the use of serum insubetween these groups. The PSA level and age of the patients diCered significantly between the groups (both lin-like growth factor 1 (IGF-1) levels is more eBcient than serum prostate specific antigen (PSA) levels in P<0.001). There was no correlation between IGF-1 and PSA levels, and even when the age diCerence in predicting prostate cancer in patients undergoing prostatic biopsy.the groups was considered, there was still no significant relationship between I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
1
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 34 publications
4
26
1
1
Order By: Relevance
“…Chan et al (32) reported an association between serum IGF-I levels and the risk of prostate cancer. However, in other studies, a direct correlation between prostate cancer and serum IGF-I could not be found (33,34). IGF-II also plays a critical role in the autocrine and paracrine stimulation of prostatic neoplasms.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Chan et al (32) reported an association between serum IGF-I levels and the risk of prostate cancer. However, in other studies, a direct correlation between prostate cancer and serum IGF-I could not be found (33,34). IGF-II also plays a critical role in the autocrine and paracrine stimulation of prostatic neoplasms.…”
Section: Discussionmentioning
confidence: 84%
“…There is a lack of consensus regarding the influence of IGF-I on the etiology of prostate cancer (29)(30)(31)(32)(33)(34). Chan et al (32) reported an association between serum IGF-I levels and the risk of prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Уже более десяти лет ведутся активные исследования, направленные на установление ассоциации риска РПЖ с уровнем белков IGF1 и IGFBP3, относящихся к системе инсулино-подобных факторов роста и участвующих в реализации пролиферативных и подавляющих апоптоз каскадных путей [18,20,21]. В нашей выборке средний сывороточный уровень IGF1 у больных РПЖ составил 97,35 нг/мл, тогда как у больных ДГПЖ -90,05 нг/мл.…”
Section: рисунокunclassified
“…However, a growing body of evidence suggests that serum insulin-like growth factor 1 (IGF-1) and insulin-like growth factor binding protein-3 (IGFBP-3) levels may play a role in prostate cancer risk and/or severity (5,6). Previous findings relating circulating levels of IGF-1 and IGFBP-3 to prostate cancer risk and severity have been intriguing, although not entirely consistent (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). Of note, a positive association between increased IGF-1 levels and prostate cancer was found in three prospective studies (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%